Transforming Institutions and Strengthening Livelihoods in Emerging Regional Spaces: A Case Study from Indonesia - Syakirotin, Muthiah; Sulistyowati, Lies; Insan Noor, Trisna; Choibar Tridakusumah, Ahmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Indonesia’s policy of regional expansion, initiated after the 1998 reform and formalized through Law No. 22/1999, was intended to address regional development inequalities. However, it has often led to land-use changes that pose risks to agricultural livelihoods, especially in newly established regions such as Pangandaran Regency. This research investigates the dimensions of livelihood vulnerability, the roles of institutional and policy frameworks, the composition of livelihood capital, the sustainability of livelihoods, and the prevalence of poverty in Pangandaran. Employing a quantitative descriptive approach, the study surveyed 378 farming households across the Mangunjaya and Padaherang Sub-Districts. The analysis reveals that sensitivity is the most dominant factor in livelihood vulnerability; environmental legal frameworks are the strongest among institutional and policy elements; financial capital is the most prevalent form of livelihood asset; land-use-related ecological factors are the most vital to sustainability; and housing conditions emerge as the key indicator of poverty. These findings emphasize the intricate interplay between institutional change and rural livelihoods, and they point to the critical need for cohesive policies that promote sustainable agriculture amid the ongoing challenges of regional development.